Ambulatory quality, special health care needs, and emergency department or hospital use for US children. (27th June 2020) - Coller, Ryan J.; Kelly, Michelle M.; Sklansky, Daniel J.; Shadman, Kristin A.; Ehlenbach, Mary L; Barreda, Christina B.; Chung, Paul J.; Zhao, Qianqian; Edmonson, Marshall Bruce
Abstract: Objective: This study examined family‐reported ambulatory care quality and its association with emergency department and hospital utilization, and how these relationships differed across levels of medical complexity. Data sources: The 2006‐2013 Medical Expenditure Panel Survey (MEPS). Study Design: Secondary analysis of MEPS data. Variables fitting the National Quality Measures Clearinghouse clinical quality measures domain framework were selected. Exploratory factor analysis grouped ambulatory quality into 12 access, experience, or process measures. Weighted negative binomial regression stratified by health status identified associations between ambulatory quality and ED visits or hospitalizations. Data Collection: 41, 497 children ≤18 years were included. The 5‐item special health care needs (SHCN) screener categorized health status as complex, less complex, or no SHCN. Principal Findings: Weighted SHCN proportions were 1.6 Percent complex, 18.2 Percent less complex, and 80.0 Percent no SHCN. Mean ED visits were 130 and 335 visits/1000 children/year for no/ complex SHCN, respectively. Mean hospitalizations were 20 and 175 hospitalizations/1000 children/year for no/complex SHCN, respectively. ED visits were associated with 8 of 12 quality measures for no/less complex SHCN. For example, usually/always receiving needed care right away was associated with 22 Percent lower ED visit rate (95% CI 0.64‐0.96). Hospitalizations were associated with 4 of 12 quality measures for less complex SHCN. In complex SHCN, associations between ambulatory quality and ED/hospital use were weak and inconsistent. Conclusions: Ambulatory quality may best predict ED and hospital use for children with no or less complex SHCN. Whether and how ambulatory care predicts emergency and hospital care in complex SHCN remains an important question.